Liver X Receptor Alpha Is Important in Maintaining Blood-Brain Barrier Function - Wouters, Elien; de Wit, Nienke M.; Vanmol, Jasmine; van der Pol, Susanne M. A.; van het Hof, Bert; Sommer, Daniela; Loix, Melanie; Geerts, Dirk; Gustafsson, Jan Ake; Steffensen, Knut R.; Vanmierlo, Tim; Bogie, Jeroen F. J.; et al. (Frontiers in Immunology, 2019)
Dysfunction of the blood-brain barrier (BBB) contributes significantly to the pathogenesis of several neuroinflammatory diseases, including multiple sclerosis (MS). Potential players that regulate BBB function are the liver X receptors (LXRs), which are ligand activated transcription factors comprising two isoforms, LXRα, and LXRβ. However, the role of LXRα and LXRβ in regulating BBB (dys)function during neuroinflammation remains unclear, as well as their individual involvement. Therefore, the goal of the present study is to unravel whether LXR isoforms have different roles in regulating BBB function under neuroinflammatory conditions. We demonstrate that LXRα, and not LXRβ, is essential to maintain barrier integrity in vitro. Specific knockout of LXRα in brain endothelial cells resulted in a more permeable barrier with reduced expression of tight junctions. Additionally, the observed dysfunction was accompanied by increased endothelial inflammation, as detected by enhanced expression of vascular cell adhesion molecule (VCAM-1) and increased transendothelial migration of monocytes toward inflammatory stimuli. To unravel the importance of LXRα in BBB function in vivo, we made use of the experimental autoimmune encephalomyelitis (EAE) MS mouse model. Induction of EAE in a constitutive LXRα knockout mouse and in an endothelial specific LXRα knockout mouse resulted in a more severe disease score in these animals. This was accompanied by higher numbers of infiltrating leukocytes, increased endothelial VCAM-1 expression, and decreased expression of the tight junction molecule claudin-5. Together, this study reveals that LXRα is indispensable for maintaining BBB integrity and its immune quiescence. Targeting the LXRα isoform may help in the development of novel therapeutic strategies to prevent BBB dysfunction, and thereby neuroinflammatory disorders.